9 is the answer for that problem
Answer:
(1,6) & (7,0)
Step-by-step explanation:
y = -x + 7
y = -0.5(x - 3)² + 8
To solve the system, solve these two equations simultaneously
-x + 7 = -0.5(x - 3)² + 8
-x + 7 = -0.5(x² - 6x + 9) + 8
-x + 7 = -0.5x² + 3x - 4.5 + 8
0.5x² - 4x + 3.5 = 0
x² - 8x + 7 = 0
x² - 7x - x + 7 = 0
x(x - 7) - (x - 7) = 0
(x - 1)(x - 7) = 0
x = 1, 7
y = -1 + 7 = 6
y = -7 + 7 = 0
(1,6) (7,0)
Since the system has two distinct solutions, the line and the curve meet at two distinct poibts9: (1,6) & (7,0)
Answer: 0.4127
Step-by-step explanation:
The probability formula to find p(F/E):
p(F/E)= N(E n F) / N(E)
p(F/E)= 260 / 630
p(F/E) = 0.4127
Answer:
The answer is B.
Step-by-step explanation:
Any percentage is a number divided by 100 . So 0.4%=0.4100 . Dividing 0.4 by 100 gives 0.004 .
Answer:
Option C.
Step-by-step explanation:
We start with the expression:
![\sqrt{y^3} + \sqrt{16*y^3} - 4*y\sqrt{y}](https://tex.z-dn.net/?f=%5Csqrt%7By%5E3%7D%20%20%2B%20%5Csqrt%7B16%2Ay%5E3%7D%20-%204%2Ay%5Csqrt%7By%7D)
where y > 0. (this allow us to have y inside a square root, so we don't mess with complex numbers)
We want to find the equivalent expression to this one.
Here, we can do the next two simplifications:
![\sqrt{16*y^3} = \sqrt{16} \sqrt{y^3} = 4*\sqrt{y^3}](https://tex.z-dn.net/?f=%5Csqrt%7B16%2Ay%5E3%7D%20%3D%20%5Csqrt%7B16%7D%20%5Csqrt%7By%5E3%7D%20%3D%204%2A%5Csqrt%7By%5E3%7D)
And:
![y*\sqrt{y} = \sqrt{y^2} *\sqrt{y} = \sqrt{y^2*y} = \sqrt{y^3}](https://tex.z-dn.net/?f=y%2A%5Csqrt%7By%7D%20%3D%20%5Csqrt%7By%5E2%7D%20%2A%5Csqrt%7By%7D%20%3D%20%5Csqrt%7By%5E2%2Ay%7D%20%3D%20%5Csqrt%7By%5E3%7D)
If we apply these two to our initial expression, we can rewrite it as:
![\sqrt{y^3} + \sqrt{16*y^3} - 4*y\sqrt{y}](https://tex.z-dn.net/?f=%5Csqrt%7By%5E3%7D%20%20%2B%20%5Csqrt%7B16%2Ay%5E3%7D%20-%204%2Ay%5Csqrt%7By%7D)
![\sqrt{y^3} + 4*\sqrt{y^3} - 4\sqrt{y^3} = \sqrt{y^3}](https://tex.z-dn.net/?f=%5Csqrt%7By%5E3%7D%20%20%2B%204%2A%5Csqrt%7By%5E3%7D%20-%204%5Csqrt%7By%5E3%7D%20%3D%20%5Csqrt%7By%5E3%7D)
Here we can use the second simplification again, to rewrite:
![\sqrt{y^3} = y*\sqrt{y}](https://tex.z-dn.net/?f=%5Csqrt%7By%5E3%7D%20%3D%20y%2A%5Csqrt%7By%7D)
So, concluding, we have:
![\sqrt{y^3} + \sqrt{16*y^3} - 4*y\sqrt{y} = y*\sqrt{y}](https://tex.z-dn.net/?f=%5Csqrt%7By%5E3%7D%20%20%2B%20%5Csqrt%7B16%2Ay%5E3%7D%20-%204%2Ay%5Csqrt%7By%7D%20%3D%20y%2A%5Csqrt%7By%7D)
Then the correct option is C.